AN INVESTIGATION OF A LITERARY TRANSLATOR’S STYLE IN A NOVEL WRITTEN BY JORGE AMADO - Camargo, Diva Cardoso de (Intercâmbio, 2010)
Our study is based on Berber Sardinha’s and Baker’s proposals in order to create a Brazilian Portuguese parallel corpus built in electronic format as well as carry out observation of a literary translator’s use of linguistic patterns in terms of type/token ratio in a translation of Jorge Amado’s novel.